STRUKTUR KOMUNITAS ECHINODERMATA PADA EKOSISTEM LAMUN DI GILI GEDE, LOMBOK BARAT, NUSA TENGGARA BARAT - Darma Prasetio; Ratna Suharti; Hendra Irawan; Aditya Bramana; Meuthia Aula Jabbar; Dadan Zulkifli; Siti Mira Rahayu (Universitas Mataram, 2024)
Ecologically Echinoderms plays a role as a eater of organic waste or detritus originating from animal and plant remains to clean organic waste in the ocean, one of the echinoderm habitats is in the seagrass ecosystem. The aim of this research is to determine seagrass density and abundanceechinoderms, biological index (Diversity, uniformity and dominance) of seagrasses and echinoderms and water conditions. The seagrass and echinoderm data collection method uses a 100 meter perpendicular transect with a 1 x 1 m² quadrant tansec plot toechinoderms and quadrant 50 x 50 cm² for seagrass. Density of seagrass species at station II Halophila ovalis with a value of 1,294.2 ind/m2 and station III of the type Halophila minor, Halodule pinifolia, andSyringodium isoetifolium and station IV typeHalophila ovalis with a specific density of 0 ind/m2. The distribution of echinoderms found at the four observation stations was divided into 18 types from the 5 classes of echinoderms found, the highest type found was at station IV with a total of 588 ind/m² and the lowest was at station III with a total of 85 ind/m².